Penerapan Multi-Atributive Ideal-Real Comparative Analysis dan PIPRECIA Dalam Evaluasi Kinerja Pemasok Bahan Baku - Pasha, Donaya; Safi, Mudar; Setiawansyah (STMIK Budi Darma, 2024)
Performance evaluation of raw material suppliers is a systematic process carried out by companies to measure and monitor supplier performance in supplying the necessary raw materials. Through continuous evaluation, companies can improve the effectiveness of supplier management strategies, identify opportunities for improvement, and build long-term, mutually beneficial relationships. Performance evaluation of raw material suppliers is the main instrument in maintaining supply chain integrity and ensuring the sustainability of company operations. This process involves assessing various aspects, including the quality of raw materials, timeliness of delivery, compliance with ethical and environmental standards, and efficiency in logistics processes. The problem that occurs in performance evaluation is that there is no application of a decision support system model that can evaluate the performance of raw material suppliers, the process so far carried out in evaluating the performance of raw material suppliers only assesses the criteria in the assessment of supplier performance evaluation. This study aims to evaluate the performance of raw material suppliers by applying the Multi-Attributive Ideal-Real Comparative Analysis (MAIRCA) method and Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA). The final value of supplier performance evaluation is the overall result of the appraisal process carried out by a company on its suppliers. In this process, various aspects of supplier performance are evaluated using predetermined methods, the PIPRECIA method for weighting criteria and MAIRCA for supplier performance evaluation calculations. The results of the evaluation of the performance of raw material suppliers show the results for the best 1 with a final value of 0.352 obtained by Tanjung Raja suppliers, the best 2 with a final value of 0.333 obtained by CV Tri Sakti suppliers, the best 3 with a final value of 0.315 obtained by Abadi Makmur suppliers.